Mesolithic Occupations During the Boreal Climatic Fluctuations at La Baume de Monthiver (Var, France) - Ricci Giulia; Audiard Benjamin; Tomasso Antonin; Hoareau Leïla; Julien Marie-Anne; Mologni Carlo; Purdue Louise; Porraz Guillaume (Open Archaeology, 2023)
The Mesolithic technology in Western Europe depicts the last cultural expressions and adaptations of hunter-gatherers before the adoption of Neolithic agro-pastoral practices. Many questions arise when investigating the timing, nature, and historical significance of the Mesolithic. The development of the Mesolithic culture is usually associated with the onset of milder environmental conditions at the beginning of the Holocene. Hunter-gatherer societies would have adopted new subsistence and territorial strategies in response to environmental changes, which would have consecutively impacted their technological system. This assertion considers the Mesolithic in South-western Europe as one homogeneous phenomenon and eludes the putative role that early Holocene climatic fluctuations may have played in hunter-gatherer organizations. In this study, we aimed at questioning the archaeological variability of the first Mesolithic by taking benefit from new data provided by recent excavations at La Baume de Monthiver (Comps-sur-Artuby, France). La Baume de Monthiver is a small rock shelter located along the Jabron Valley in the southern French pre-Alps. The rock shelter records several Mesolithic occupations documenting Sauveterrian technological traditions. By studying the Baume de Monthiver, we take the opportunity to explore the Sauveterrian in its longue durée and address the question of its diachronic variability. In this study, we investigated the M-B′ archaeological assemblage and question its homogeneity at the transition of the 10th- and 9th-millennium cal. BP. Our results document stable technological and subsistence practices before and after the climatic fluctuations at the end of the 10th-millennium cal. BP, supporting the hypothesis of well-adapted Mesolithic societies to the climatic “instability” characterizing the early Holocene.